Ater-Ater Tradition as an Islamic Education Approach to Strengthen Religious Identity - Saeful Fikri (Yayasan Adra Karima Hubbi, 2024)
The ater-ater tradition is a tradition that is still carried out by the people of Malang in particular. This is because the tradition has a close relationship with their beliefs, namely Islam. This article aims to explore the ater-ater tradition as an Islamic education approach to strengthen religious identity. The method used in this research is a qualitative method with data collection methods through observation, interviews and documentation. This is done in order to see social phenomena from the participants' point of view. The results showed that the ater-ater tradition is a tradition carried out on religious holidays such as Eid al-Fitr, Eid al-Adha, Maulid Nabi, Isra Mi'raj, the month of Sha'ban and the night of Lailatul Qodr. The tradition is carried out in the form of giving food to relatives and community leaders. In their view, this ater-ater tradition is carried out with the intention and purpose of strengthening the relationship. By doing the ater-ater tradition they believe and fully believe that it will bring abundant fortune, long life and also avoid various disasters and dangers. Thus it can be concluded that this ater-ater tradition is a tradition that contains a very high value of empathy and sympathy as well as teaching someone to avoid individualism. This is in accordance with the philosophy of Islam which teaches humans to always maintain friendship so that empathy and sympathy are embedded in themselves.